2017
DOI: 10.1111/eva.12574
|View full text |Cite
|
Sign up to set email alerts
|

Empirical and theoretical investigation into the potential impacts of insecticide resistance on the effectiveness of insecticide‐treated bed nets

Abstract: In spite of widespread insecticide resistance in vector mosquitoes throughout Africa, there is limited evidence that long‐lasting insecticidal bed nets (LLINs) are failing to protect against malaria. Here, we showed that LLIN contact in the course of host‐seeking resulted in higher mortality of resistant Anopheles spp. mosquitoes than predicted from standard laboratory exposures with the same net. We also found that sublethal contact with an LLIN caused a reduction in blood feeding and subsequent host‐seeking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 46 publications
(69 reference statements)
6
60
0
Order By: Relevance
“…Females that were exposed to deltamethrin fed less than females that were not exposed. Our findings were consistent with Glunt et al, [26] and contrary to what was observed by Tchakounte et al, [27] who showed that exposure of mosquitoes to PermaNet 2.0 deltamethrintreated bednet presented no effect of on their blood feeding ability. From an epidemiological point of view, our findings can be translated into a reduction in transmission as the drop in the rate of mosquito bites also means less risk of infection with plasmodium.…”
Section: Discussionsupporting
confidence: 93%
“…Females that were exposed to deltamethrin fed less than females that were not exposed. Our findings were consistent with Glunt et al, [26] and contrary to what was observed by Tchakounte et al, [27] who showed that exposure of mosquitoes to PermaNet 2.0 deltamethrintreated bednet presented no effect of on their blood feeding ability. From an epidemiological point of view, our findings can be translated into a reduction in transmission as the drop in the rate of mosquito bites also means less risk of infection with plasmodium.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that deltamethrin-treated nets reduced blood-feeding of Anopheles, suggesting that this inhibition could be due to contact irritancy [37,40]. In a similar study to ours, Glunt et al [11] also found blood-feeding inhibition in SENN-DDT (1×), FUMOZ (5×), and FUMOZ-R (10×) when mosquitoes were given access to a host after LLIN exposure (and not during exposure). Surprisingly, our results show a much higher feeding compliance in FUMOZ-R on the LLIN than on the untreated net in the tent assay, for which we do not have a good explanation.…”
Section: Discussionsupporting
confidence: 81%
“…Other studies, however, have found that LLINs are still more effective in preventing both clinical and subclinical malaria infections than untreated nets in areas with high pyrethroid resistance [5][6][7][8], including a 4-year WHO-coordinated 5-country cohort study that found no association between pyrethroid resistance and malaria incidence or prevalence in the field [9]. While observational studies need to be treated with caution as they cannot control for various factors and tend to only assess personal protection (a modeling analysis suggests that there could be loss of community protection even if levels of personal protection from LLINs remains high [10]), there are clearly complexities in interpreting the epidemiological consequences of resistance [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glunt et al. () further discuss the challenges of insecticide resistance in the context of malaria, with a specific focus on pyrethroids impregnated long‐lasting insecticidal bed nets (LLINs) and their efficacy in preventing malaria. About 1 billion LLINs, a major vector control tool, have been distributed in Africa in the last 10 years.…”
Section: Themes Of the Special Issuementioning
confidence: 99%